Photo-inactive divinyl spiropyran mechanophore cross-linker for real-time stress sensing. (2nd September 2016) - Li, Meng; Zhang, Qi; Zhu, Shiping
Abstract: In this work, we study the mechanical activation of a new type of spiropyran mechanophore cross-linker, (1′-(2-(methacryloyloxy)ethyl)-3′, 3′-dimethylspiro[chromene-2, 2′-indolin]-6-yl)methyl methacrylate (MA-SP3-MA ) in poly methyl acrylate (PMA), prepared via free radical polymerization. Compared with other SPs, SP3 mechanophore shows two unique features. First, the films exhibit good sensitivity towards mechanical force but not to UV irradiation. Second, the merocyanine (MC)-to-SP reversion in PMA films after relaxation was very fast. Further, the mechanical activation can be repeated for three times but with diminishing of peak color, caused by the damage of overstrained polymer chains. We also observe that increasing SP content leads to stiffer and more rigid elastomer as well as earlier threshold strain for activation point of SP to MC but has little effect on threshold stress for SP activation. This work offers inspirations towards mechanophore design for polymeric materials to broaden the scope of potential applications of mechanophores. Graphical abstract: Highlights: A mechanophore cross-linker (MA-SP3-MA) was synthesized and employed in free radical polymerization of methyl acrylate. The SP3 cross-linker has two important features: sensitivity to mechanical force but not to UV and fast recovery rate. Increasing SP3 content leads to stiffer, lower Tg and earlier threshold strain for SP activation in PMA. Threshold stress for SP3 cross-linked PMA is 6.7∼7.1 MPa.